A family with Charcot-Marie-Tooth disease (type 1): evaluating diagnostic role of nerve conduction studies - Gupta, Sangeeta; Gupta, Gaurav; Wadoo, Ovais Karnain; Singh, Surjit (International Journal of Research in Medical Sciences, 2017)
We aimed to report a case history of a family with Charcot-Marie-Tooth disease and to assess the role of nerve conduction studies in the diagnosis. A 10-year-old girl presented with difficulty in walking with a history of delayed motor milestones and slowly progressive weakness in distal muscles of both the lower limbs, with similar group of complaints in her father and a younger brother. Clinical examination of the patients was done and nerve conduction studies were performed. Clinical features and nerve conduction studies suggested the diagnosis as Charcot-Marie-Tooth disease with characteristic electro-diagnostic findings of Charcot-Marie-Tooth disease type-1. Charcot-Marie-Tooth disease is a rare disorder found in India. Although genetic tests form the basis of accurate diagnosis, yet nerve conduction studies, to a great extent, prove to be remarkable in approaching the diagnosis and distinguishing the common subtypes of this rare condition.